THE PREVALENCE OF CHRONIC ANKLE INSTABILITY IN HIGH SCHOOL BASKETBALL ATHLETE AT BADUNG REGENCY - Prasada, Vimala Krishna; Tianing, Ni Wayan; Saraswati, Putu Ayu Sita; Sutadarma, I Wayan Gede (Majalah Ilmiah Fisioterapi Indonesia; Vol 8 No 1 (2020): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2020.v08.i01.p03, 2020)
Ankle injury is the most common injury experienced by basketball athletes, and the sprain in the lateral ligament is the most common diagnosis. This can cause an athlete to experience chronic ankle instability (CAI). This condition is characterized by repeated injuries and a sensation of giving way of the ankle. The purpose of this study was to determine the prevalence of chronic ankle instability in high school basketball athletes in Badung Regency. This research is a cross-sectional descriptive study conducted from March to May 2019. Sampling used purposive sampling technique with a total sample of 162 people. The Cumberland Ankle Instability Tool questionnaire was used to determine respondents who experienced CAI. Other factors such as gender, body mass index (BMI), history of ankle sprain injury, and the presence or absence of medical treatment after an ankle sprain injury were also noted in this study. The results showed a prevalence of chronic ankle instability of 51.2%. Respondents with male sex, overweight BMI, having a history of ankle sprain and obtaining medical treatment after an ankle sprain injury had a greater tendency to experience CAI. Keywords: Chronic Ankle Instability, High School Basketball Athlete